1993
DOI: 10.1161/01.str.24.5.647
|View full text |Cite
|
Sign up to set email alerts
|

Silent brain infarctions in patients with first-ever stroke. A community-based study in Umbria, Italy.

Abstract: Background and Purpose: The relative frequency of computed tomographic evidence of old cerebral infarctions without prior history of stroke, and their effect on short-and long-term outcome of patients with first-ever ischemic stroke, are currently unknown. Silent infarctions may relate to specific risk factors and may influence the rate of survival free of handicap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 23 publications
2
52
0
Order By: Relevance
“…CT studies among patients admitted with acute stroke but no history of prior stroke, for example, have demonstrated that 10% to 38% of such patients have evidence of prior infarction. 76,88,90 In 1 study, silent infarcts on CT were seen among 15% of patients with asymptomatic carotid stenosis. 91 Vermeer et al 74 reviewed the literature on MR-detected silent infarcts (n=105 original papers) in 2007.…”
Section: 88mentioning
confidence: 97%
“…CT studies among patients admitted with acute stroke but no history of prior stroke, for example, have demonstrated that 10% to 38% of such patients have evidence of prior infarction. 76,88,90 In 1 study, silent infarcts on CT were seen among 15% of patients with asymptomatic carotid stenosis. 91 Vermeer et al 74 reviewed the literature on MR-detected silent infarcts (n=105 original papers) in 2007.…”
Section: 88mentioning
confidence: 97%
“…The prevalence of silent lesions in previous CT or MRI studies varies from 10% to 47%, [6][7][8][9]23,24 and populationbased studies using MRI report a prevalence of silent lesions ranging from 11% to 28%. 2,25,26 In the present study, the prevalence of silent lesions by MRI, especially those ≥3 mm, was 44.9% in control patients, which is relatively high compared with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The reported prevalence of silent lesions observed by MRI varies, 3,[6][7][8][9] but there is consensus that it is high in elderly subjects and in patients with risk factors for stroke (eg, hypertension and atrial fibrillation (AF)). 1,4,10,11 The importance of these silent lesions has been emphasized in reports linking them to impaired cognition 2 and depression.…”
mentioning
confidence: 99%
“…Herderschee et al 3 found silent infarction in 11% of 2329 patients participating in a secondary prevention trial, but only patients with TIA and minor stroke were included, and the study was not community-based. Ricci et al 4 found in a community-based study silent infarction to be present in 80 (38%) of 209 patients with first-ever stroke. However, only 56% of the patients had CT scan, and silent infarcts were diagnosed just as frequently as symptomatic infarcts.…”
Section: Prevalencementioning
confidence: 98%
“…Information concerning the influence of silent infarction on stroke outcome is, however, sparse. Ricci et al 4 found that poor outcome, defined as death or persistence of physical handicap, was not influenced by the presence of silent infarction. However, smaller differences in outcome or in the speed of recovery caused by silent infarction might not be recognized with these end points.…”
mentioning
confidence: 99%